2020
DOI: 10.1073/pnas.2004112117
|View full text |Cite
|
Sign up to set email alerts
|

Lsh/HELLS is required for B lymphocyte development and immunoglobulin class switch recombination

Abstract: Mutation of HELLS (Helicase, Lymphoid-Specific)/Lsh in human DNA causes a severe immunodeficiency syndrome, but the nature of the defect remains unknown. We assessed here the role of Lsh in hematopoiesis using conditional Lsh knockout mice with expression of Mx1 or Vav Cre-recombinase. Bone marrow transplantation studies revealed that Lsh depletion in hematopoietic stem cells severely reduced B cell numbers and impaired B cell development in a hematopoietic cell-autonomous manner. Lsh-deficient mice without bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 68 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…1e ). Genomic instability, however, was not associated with substantial increases in cell death, since LSH-deficient B cells display no significant differences in cellular growth and survival rates in vitro when compared to LSH-proficient cells 14 . Altogether, our data revealed increased signs of DNA damage and genomic instability in proliferating LSH-deficient lymphocytes.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…1e ). Genomic instability, however, was not associated with substantial increases in cell death, since LSH-deficient B cells display no significant differences in cellular growth and survival rates in vitro when compared to LSH-proficient cells 14 . Altogether, our data revealed increased signs of DNA damage and genomic instability in proliferating LSH-deficient lymphocytes.…”
Section: Resultsmentioning
confidence: 90%
“…We used conditional Lsh knockout mice with Lsh gene depletion in the hematopoietic system to investigate signs of genomic instability in LSH-KO and control lymphocytes (Supplementary Fig. 1a ) 14 . Using immunofluorescence analysis, we found that LSH-deficient lymphocytes, stimulated with either B (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HELLS is a multifunctional protein proved to play, among the others, critical roles in DNA methylation, chromatin packaging, and development of lymphoid tissue 47 . Known also as Lymphoid-specific helicase (Lsh) HELLS is required for normal development and survival of lymphoid and other tissues via chromatin organization 48 49 , promotion of DNA double-strand break repair 50 , 51 and chromatin accessibility modification 52 , 53 . In cancer, HELLS is deregulated in several settings i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that this complex facilitates the nonhomologous end joining (NHEJ) of double-strand breaks (DSBs) by enhancing access of Ku80 (also called XRCC5), a factor essential for NHEJ by protecting DSB ends from resection, to the sites of DSBs, and potentially suppresses many cytological defects; ZBTB24 KO, CDCA7 KO, and HELLS KO human embryonic kidney 293 (HEK293) cells generated using the CRISPR/ Cas9 system displayed enlarged nuclei, centrosome amplification, abnormal chromosome segregation, and many related phenotypes, including proliferation defects, aneuploidy, and apoptosis (Unoki et al, 2019). Recently, it was reported that ZBTB24 and HELLS are essential for NHEJ during immunoglobulin class-switch recombination (He et al, 2020;Helfricht et al, 2020). Taken together, these findings indicate that ZBTB24, CDCA7, and HELLS are largely involved in the same biological pathway, although they also have their specific functions; for example, (Jarvis et al, 1996) Genes to Cells UNOKI ZBTB24 works not only as a transcriptional activator of CDCA7, but also as a direct regulator of poly(ADP-ribose) polymerase 1 (PARP1)-dependent NHEJ and class-switch recombination (Helfricht et al, 2020).…”
Section: Genes Of Icf Syndromementioning
confidence: 99%